2021
DOI: 10.3389/fsufs.2021.732831
|View full text |Cite
|
Sign up to set email alerts
|

A Living Income for Cocoa Producers in Côte d'Ivoire and Ghana?

Abstract: It is often claimed that cocoa producers are poor, but the extent of their poverty is rarely defined. We analyzed six data sets derived from household questionnaires of 385–88,896 cocoa producers in Côte d'Ivoire and Ghana. Across all data sets, many households (30–58%) earn a gross income below the World Bank extreme poverty line and the majority (73–90%) do not earn a Living Income. Households with less income per person per day generally achieve lower cocoa yields, consist of more household members, have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Between 35% to 45% of all cocoa farmers are estimated to live below the poverty line, and up to 90% of farmers do not earn a living income. 10 Low farmer incomes are also at the root of other sustainability challenges in the Ghanaian cocoa sector, including child labor and deforestation. 11 Several structural challenges continue to combine to significantly affect productivity and sustainability of the sector overall.…”
Section: Figure 2 the Three Dimensions Of Companies' Living Income St...mentioning
confidence: 99%
“…Between 35% to 45% of all cocoa farmers are estimated to live below the poverty line, and up to 90% of farmers do not earn a living income. 10 Low farmer incomes are also at the root of other sustainability challenges in the Ghanaian cocoa sector, including child labor and deforestation. 11 Several structural challenges continue to combine to significantly affect productivity and sustainability of the sector overall.…”
Section: Figure 2 the Three Dimensions Of Companies' Living Income St...mentioning
confidence: 99%
“…According to the Livelihood Funds report on smallholder farmers in 2021, the typical yearly profit from cocoa production for smallholder farmers was about 1,275 dollars equivalent, something that is considerably lower than the decent living income estimated at about 2,200 dollars per year, making smallholders unable to make investments in the development of their farms. Furthermore, Van Vliet et al (2021) reported that the incomes of 73 to 90% of cocoa farming households do not meet the standard of living. According to Bymolt et al (2018), cocoa farming households in Ghana typically rely heavily on income from cocoa sales, which accounts for 61% of total household income on average.…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, cocoa ( Theobroma cacao L.) is a widely cultivated crop, and as the nation's primary export commodity, it has a significant economic impact on the nation and an even greater socioeconomic impact on the cocoa-growing farmers and villages [ [1] , [2] , [3] , [4] ]. Ghana is the second-largest cocoa-producing country in the world, and merged with Côte d’Ivoire, produces about 70% of the world's cocoa [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%